Analysis of the Influence of Renewable Generator Frequency Endurance Capability on Low-Frequency Load Shedding: A Hunan Case Study - Yang-Wu Shen; Ding Wang; Hao Chen; Jian Zuo; Min Xu; Wei Cao (Complexity)
With the rapid development of renewable generators such as distributed photovoltaic and profound changes of the power structure, this paper analyzes the frequency characteristics of the power system with high penetration of renewable generations in the process of low-frequency load shedding and discusses the influence of the distributed renewable generator frequency endurance capabilities on the implementation effect of low-frequency load shedding in detail. Finally, the influences of the distributed renewable generator frequency endurance capability and the capacities of the distributed renewable generator on frequency response characteristics of an actual Hunan power grid are simulated. The simulation results show that more distributed photovoltaic capacity without frequency endurance capability leads to deeper frequency drops after the disturbance and requires more basic rounds of load shedding. When the penetration rate of distributed photovoltaic is too high, it may cause load shedding, resulting in power grid load losses and, at the same time, leading to an overshoot phenomenon in the process of frequency recovery. Therefore, the influence of distributed photovoltaic on the control of low-frequency load shedding should be considered when designing low-frequency load shedding schemes for the power grid with high penetration of distributed photovoltaic.